Accelerating the integration of China into the global development of innovative anticancer drugs. Issue 11 (November 2022) - Huang, Huiyao; Wu, Dawei; Miao, Huilei; Tang, Yu; Liu, Chengcheng; Fang, Hong; Meng, Xinyu; Wang, Shuhang; Zhu, Qi; Wang, Xin; Du, Jingting; Yang, Zhimin; et al.
Summary: The aim of this Policy Review was to compare China's overall and synchronous participation in clinical trials for innovative anticancer drugs with that of the USA, the EU, Japan, and South Korea, and to assess changes in the participation rate trends in these five regions. Relevant data from the top 20 international pharmaceutical companies from 2011 to 2021 were systematically collected from the Trialtrove and Pharmaprojects databases. Among the 8260 trials for 954 new anticancer drugs identified, China was involved in 8·8% of the trials and with 20·4% of the drugs being trialled. These participation rates are significantly lower than those for South Korea (14·5% of trials and 36·3% of drugs), Japan (16·1% of trials and 38·7% of drugs), the EU (40·6% of trials and 67·7% of drugs), and the USA (65·7% of trials and 91·2% of drugs; p<0·0001 for all). Similar results were found for the synchronous participation rate, defined as the proportion of drugs or trials at the highest development stage internationally, for the 803 tested drugs, which ranged from 9·0% in China to 87·7% in the USA. China's participation rate in early phase trials (4·4%) and in synchronous trials (5·4%) was even lower, in stark contrast to that of the USA (66·1% for early phase trials and 89·1% for synchronous trials). The fastest growing annual rate of participation in trials was observed in China (15·7%), followed by South Korea (8·2%) and Japan (6·8%); no change was detected in the USA or the EU. This Policy Review shows that Chinese participation in the clinical development of innovative cancer drugs by international pharmaceutical companies has increased over the past decade, but an obvious gap persists in comparison with the USA, the EU, Japan, and South Korea, especially in its synchronous participation and early participation rates.